Α1‐Adrenergic Receptors Function Within Hetero‐Oligomeric Complexes With Atypical Chemokine Receptor 3 and Chemokine (C‐X‐C motif) Receptor 4 in Vascular Smooth Muscle Cells. Issue 8 (17th August 2017) - Albee, Lauren J.; Eby, Jonathan M.; Tripathi, Abhishek; LaPorte, Heather M.; Gao, Xianlong; Volkman, Brian F.; Gaponenko, Vadim; Majetschak, Matthias
Abstract : Background: Recently, we provided evidence that α1 ‐adrenergic receptors (ARs) in vascular smooth muscle are regulated by chemokine (C‐X‐C motif) receptor (CXCR) 4 and atypical chemokine receptor 3 (ACKR3). While we showed that CXCR4 controls α1 ‐ARs through formation of heteromeric receptor complexes in human vascular smooth muscle cells (hVSMCs), the molecular basis underlying cross‐talk between ACKR3 and α1 ‐ARs is unknown. Methods and Results: We show that ACKR3 agonists inhibit inositol trisphosphate production in hVSMCs on stimulation with phenylephrine. In proximity ligation assays and co‐immunoprecipitation experiments, we observed that recombinant and endogenous ACKR3 form heteromeric complexes with α1A/B/D ‐AR. While small interfering RNA knockdown of ACKR3 in hVSMCs reduced α1B/D ‐AR:ACKR3, CXCR4:ACKR3, and α1B/D ‐AR:CXCR4 complexes, small interfering RNA knockdown of CXCR4 reduced α1B/D ‐AR:ACKR3 heteromers. Phenylephrine‐induced inositol trisphosphate production from hVSMCs was abolished after ACKR3 and CXCR4 small interfering RNA knockdown. Peptide analogs of transmembrane domains 2/4/7 of ACKR3 showed differential effects on heteromerization between ACKR3, α1A/B/D ‐AR, and CXCR4. While the transmembrane domain 2 peptide interfered with α1B/D ‐AR:ACKR3 and CXCR4:ACKR3 heteromerization, it increased heteromerization between CXCR4 and α1A/B ‐AR. The transmembrane domain 2 peptide inhibited ACKR3 but did not affect α1b ‐AR in β‐arrestin recruitment assays. Furthermore, the transmembrane domain 2 peptide inhibited phenylephrine‐induced inositol trisphosphate production in hVSMCs and attenuated phenylephrine‐induced constriction of mesenteric arteries. Conclusions: α1 ‐ARs form hetero‐oligomeric complexes with the ACKR3:CXCR4 heteromer, which is required for α1B/D ‐AR function, and activation of ACKR3 negatively regulates α1 ‐ARs. G protein–coupled receptor hetero‐oligomerization is a dynamic process, which depends on the relative abundance of available receptor partners. Endogenous α1 ‐ARs function within a network of hetero‐oligomeric receptor complexes.